A Rare Case of Fatal Endobronchial Mucormycosis Masquerading as Endobronchial Tuberculosis - Kim, Minjeong (Medicina (Kaunas), 2020)
Pulmonary mucormycosis is a relatively rare but often fatal opportunistic fungal infection that occurs mostly in immunocompromised patients. Endobronchial mucormycosis, a distinct clinical form of pulmonary mucormycosis, is very rare, and only a few cases have been reported. The most common bronchoscopic findings in patients with endobronchial mucormycosis are stenosis, erythematous mucosa and airway obstruction. Here, we present a case of fatal endobronchial mucormycosis mimicking actively caseating endobronchial tuberculosis in a young diabetic patient living in a country with an intermediate tuberculosis burden.